2011
DOI: 10.1111/j.1600-9657.2011.01007.x
|View full text |Cite|
|
Sign up to set email alerts
|

Teeth fracture among visually impaired and sighted children of 12 and 15 years age groups of Udaipur city, India - a comparative study

Abstract: Prevalence of traumatic dental injuries in a group of individuals with visual impairment was higher than that of sighted. This should alert caregivers to carry out a profound investigation of the events and suggest methods to reduce this type of morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
43
1
4

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 14 publications
6
43
1
4
Order By: Relevance
“…Studies assessing prevalence of TDI among visually impaired children also have found wide variation ranging from 9% to 32.5% [5,6,8,9]. However prevalence of TDI in our study is consistent with Bhat et al (32.5%) [6] & Agarwal et al (34.95%) [8].…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Studies assessing prevalence of TDI among visually impaired children also have found wide variation ranging from 9% to 32.5% [5,6,8,9]. However prevalence of TDI in our study is consistent with Bhat et al (32.5%) [6] & Agarwal et al (34.95%) [8].…”
Section: Discussionsupporting
confidence: 83%
“…However prevalence of TDI in our study is consistent with Bhat et al (32.5%) [6] & Agarwal et al (34.95%) [8]. Children with disabilities are more prone for TDI compared to their normal counterpart [5,8].…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations